Effectiveness Of Group-Guidance To Increase Student’s Self Confident - Irdanelli, Irdanelli; Neviyarni, Neviyarni; Syahniar, Syahniar (Universitas Negeri Padang, 2015)
As a vocational school, SMK is required to prepare the students to be professional workers having high self-confidence. Unfortunately, there were still some students having low self-confidence. This could be identified from several phenomena such as: worried of facing examination, unconfident to ask questions, unwilling to express opinion, and unwilling to answer the questions addressed to. This research was designed for revealing the effectiveness of group guidance service to improve the students’ self-confidence.This was an experimental research which applied pretest and posttest control group design. By using purposive sampling technique, the students in class XI1 majoring in Official Administration of SMK Negeri 1 Tembilahan was chosen as the experimental class, and class XI3 was taken as the control class. Each class consisted of 12 students. Group guidance service was given to the experimental group for six meetings. The data was collected through pretest and posttest. The data gained then was analyzed by using Wilcoxon Signed Ranks Test and Kolmogorov-Smirnov Two Sample assisted with SPPSS version 17.The research findings showed that: (1) there was a significant difference between the students’ self-confidence in experimental group in pretest and posttest, (2) there was a difference between the students’ self-confidence in control group in pretest and posttest, and (3) there was a significance difference between the students’ self-confidence in experimental class and in control class in posttest.Based on the research findings, it was concluded that the students’ self-confidence could be improved through group guidance service. This research suggests the importance of increasing the use of group guidance service controlled by the teachers and counselors to improve the students’ self-confidence.